2020
DOI: 10.1371/journal.pone.0236246
|View full text |Cite
|
Sign up to set email alerts
|

The bacterial potassium transporter gene MbtrkH improves K+ uptake in yeast and tobacco

Abstract: K + is an essential nutrient for plant growth and is responsible for many important physiological processes. K + deficiency leads to crop yield losses, and overexpression of K + transporter genes has been proven to be an effective way to resolve this problem. However, current research on the overexpression of K + transporter genes is limited to plant sources. TrkH is a bacterial K + transporter whose function generally depends on the regulation of TrkA. To date, whether TrkH can improve K + uptake in eukaryoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…This confirmed that overexpression of the IbHKT-like gene in sweet potato roots increased K + uptake in K + deficiency conditions. MbtrkH transgenic tobacco lines had significantly greater fresh weights, dry weights, and K + contents compared with WT tobacco lines [ 40 ]. Potassium helps sorghum plants resist drought stress and improves the content of chlorophyll and carotenoids and the activities of SOD, CAT, APX, and nitrogen metabolic enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…This confirmed that overexpression of the IbHKT-like gene in sweet potato roots increased K + uptake in K + deficiency conditions. MbtrkH transgenic tobacco lines had significantly greater fresh weights, dry weights, and K + contents compared with WT tobacco lines [ 40 ]. Potassium helps sorghum plants resist drought stress and improves the content of chlorophyll and carotenoids and the activities of SOD, CAT, APX, and nitrogen metabolic enzymes.…”
Section: Discussionmentioning
confidence: 99%